Acupuncture and related therapies for treating irritable bowel syndrome: overview of systematic reviews and network meta-analysis. (January 2019) - Wu, Irene X. Y.; Wong, Charlene H. L.; Ho, Robin S. T.; Cheung, William K. W.; Ford, Alexander C.; Wu, Justin C. Y.; Mak, Arthur D. P.; Cramer, Holger; Chung, Vincent C. H.
Background: An overview of systematic reviews (SRs) and a network meta-analysis (NMA) were conducted to evaluate the comparative effectiveness of acupuncture and related therapies used either alone, or as an add-on to other irritable bowel syndrome (IBS) treatments. Methods: A total of eight international and Chinese databases were searched for SRs of randomized controlled trials (RCTs). The methodological quality of SRs was appraised using the AMSTAR instrument. From the included SRs, data from RCTs were extracted for the random-effect pairwise meta-analyses. An NMA was used to evaluate the comparative effectiveness of different treatment options. The risk of bias among included RCTs was assessed using the Cochrane risk of bias tool. Results: From 15 SRs of mediocre quality, 27 eligible RCTs ( n = 2141) were included but none performed proper blinding. Results from pairwise meta-analysis showed that both needle acupuncture and electroacupuncture were superior in improving global IBS symptoms when compared with pinaverium bromide. NMA results showed needle acupuncture plus Geshanxiaoyao formula had the highest probability of being the best option for improving global IBS symptoms among 14 included treatment options, but a slight inconsistency exists. Conclusion: The risk of bias and NMA inconsistency among included trials limited the trustworthiness of the conclusion. Patients who did not respond well to first-line conventional therapies or antidepressants may consider acupuncture as an alternative. Future trials should investigate the potential of (1) acupuncture as an add-on to antidepressants and (2) the combined effect of Chinese herbs and acupuncture, which is the norm of routine Chinese medicine practice.